Measuring the level of voluntary disclosure in the annual reports of Islamic banks As-Salam Bank-Algeria as a model (2012-2017) - Audina, Abdelkhalek; Yahioui, Faouzi (Finance and Business Economies Review, 2020)
This study aimed to measure the level of optional disclosure in the annual reports of Al Salam Bank - Algeria during the period 2012-2017, This was based on a form consisting of 120 pieces of optional information, This study found that the level of disclosure of this information in the annual reports of Al Salam Bank-Algeria during the period 2012-2017 was weak, Considering that it did not exceed 26%, Finally, this study recommends that Al Salam Bank - Algeria and joint stock companies in general should pay more attention to voluntary disclosure due to its great importance.